2018
DOI: 10.2478/pjen-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Piper guineense Schumach. seed powder in the control of Callosobruchus maculatus (Fabricius, 1775) (Coleoptera: Chrysomelidae: Bruchinae) and on the nutritional and organoleptic characteristics of stored cowpea Vigna unguiculata (L.) Walp.

Abstract: Brown pepper (Piper guineense) seed powder, used for culinary and medicinal purposes, was evaluated in the laboratory with a conventional storage chemical, actellic 2% dust (Pirimiphos-methyl), as standard, to protect stored cowpea against the cowpea bruchid, Callosobruchus maculatus. Four rates of the seed powder were used (2.5, 5.0 and 10.0 g/100 g seed with a control, 0.0 g) while actellic dust was applied at 1.0, 2.0, 3.0 g/100 g seed and 0.0 g/100 g seed as control. Data on percentage mortality, ovipositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(25 reference statements)
2
0
0
Order By: Relevance
“…However, 3g of stem bark gave 100 % germination as against the control (93.33 %), suggesting that seeds can be stored for planting purposes. This result is in consistent with earlier works of Frank et al (2018) who reported the effect of Denettia tripetala F. and Okoye and Ebeledike (2013) who reported the effect of Mondora myristica (Gaertn.) Dunal on seed germination after storage for some period.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, 3g of stem bark gave 100 % germination as against the control (93.33 %), suggesting that seeds can be stored for planting purposes. This result is in consistent with earlier works of Frank et al (2018) who reported the effect of Denettia tripetala F. and Okoye and Ebeledike (2013) who reported the effect of Mondora myristica (Gaertn.) Dunal on seed germination after storage for some period.…”
Section: Resultssupporting
confidence: 93%
“…The reduction in numbers of eggs could be related to the early of mortality of some female or morbidity seen on male C. maculatus. The present finding is in line with that by Frank et al (2018) who reported that, Piper guineense performed better when compared with the control which he attributed to high mortality of C. maculatus that could not oviposit. Table 3 showed the effect of stem bark and pod powder on adult emergence and percentage adult emergence deterrence of C. maculatus.…”
Section: Resultssupporting
confidence: 93%